Collaborative Accountability for Sustainable Public Health: A Korean Perspective on the Effective Use of ICT-Based Health Risk Communication - Lee, Tae Jun; Park, Hyojung; Lee, Junesoo (Government Information Quarterly, 2019)
The sustainability of public health practices requires collaboration between the government and its citizens. On the government's side, social media can provide a conduit for communicating health risk information in an effective and timely fashion, while also engaging citizens in informed decision-making. On the citizen's side, information communication technology (ICT)-based practices cannot function unless citizens recognize and act on their responsibility to actively engage with government social media platforms. Despite an increasing interest in understanding the adoption of ICT practices and e-government services for health risk communication, there remains a crucial need for a comprehensive framework to explain which factors determine citizen use of digital government resources. The purpose of this study is to investigate how to increase government accountability for motivating citizens to engage in ICT-based health risk communication, thereby attaining sustainable public health practices through collaborative governance. By integrating trust and health risk information into the e-government adoption model (GAM), this research examines factors that influence citizens' likelihood of using government social media resources. Survey data from 700 Korean citizens were analyzed using structural equation modeling. The results indicated that individuals with higher social media competency are more likely to (a) seek risk information through social media and (b) perceive the government's social media sites as easy to use. Consistent with the GAM, intentions to use the government's social media sites for information and interactions appear to increase as citizens perceive more value in using them regarding information quality, ease of use, functional benefit, and security. Furthermore, perceived trust in the government's social media resources appears to function as a mediator of this process. Initial trust in the government is an important determinant of perceptions of its digital resources. Citizens who trust the government tend to evaluate new initiatives positively and are more likely to accept and make use of them. The results of this study can inform policy design and implementation by elucidating the mechanisms that determine citizens' adoption and usage of digital government services. Theoretically, this work expands the GAM to include health risk communication and adds empirical evidence to the small yet growing body of knowledge of e-government initiatives. These findings also highlight the importance of public trust in the government, as this encourages citizens to seek health risk information and assistance from the government. Overall, the data and model generated in this investigation represent an important step toward the successful and sustainable modernization of public services.